Analisis Faktor-Faktor yang Mempengaruhi Kesejahteraan Perawat - Sudrajat, Jajat; Budiman, Budiman; Rohayani, Lilis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to find out what factors influence the welfare of nurses in Bogor Regency. The research method used is correlational analysis with a cross sectional approach. The research results show that factors related to nurses' welfare are workload, training and development, team and management support, resources, recognition and appreciation and health care guarantees, involvement in decision making with a p-value <0.05. In conclusion, there is a relationship between workload, training and development, team and management support, resources, recognition and appreciation and health care guarantees, involvement in decision making on the welfare of nurses. Keywords: Workload, Health Insurance, Nurses' Welfare, Recognition and Awards, Training and Development